The comic book film adaptation : exploring modern Hollywood's leading genre - Burke, Liam (Liam P.) (University Press of Mississippi, 2015)
"In the summer of 2000 X-Men surpassed all box office expectations and ushered in an era of unprecedented production of comic book film adaptations. This trend, now in its second decade, has blossomed into Hollywood's leading genre. From superheroes to Spartan warriors, The Comic Book Film Adaptation offers the first dedicated study to examine how comic books moved from the fringes of popular culture to the center of mainstream film production. Through in-depth analysis, industry interviews, and audience research, this book charts the cause-and-effect of this influential trend. It considers the cultural traumas, business demands, and digital possibilities that Hollywood faced at the dawn of the twenty-first century. The industry managed to meet these challenges by exploiting comics and their existing audiences. However, studios were caught off-guard when these comic book fans, empowered by digital media, began to influence the success of these adaptations. Nonetheless, filmmakers soon developed strategies to take advantage of this intense fanbase, while codifying the trend into a more lucrative genre, the comic book movie, which appealed to an even wider audience. Central to this vibrant trend is a comic aesthetic in which filmmakers utilize digital filmmaking technologies to engage with the language and conventions of comics like never before.The Comic Book Film Adaptation explores this unique moment in which cinema is stimulated, challenged, and enriched by the once-dismissed medium of comics"--